COMPARATIVE STUDY OF INCIDENCE RATES AND ANTIBIOGRAM OF CATHETER-ASSOCIATED URINARY TRACT INFECTIONS IN INTENSIVE CARE UNIT VERSUS NON-INTENSIVE CARE UNIT AT A TERTIARY CARE TEACHING HOSPITAL - JOB, MICAH; MONACHAN, MOBISHA; SCARIA, RESMI; BABU, MERLIN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Catheter-associated urinary tract infections (CAUTI) is the most common HAI which leads to increased hospital stay and morbidity. The study aimed to compare the incidence rates of CAUTI per 1000 catheter days and their antimicrobial susceptibility pattern between intensive care unit (ICU) and non ICU and to determine predisposing risk factors, indications, and outcomes of CAUTI. Methods: A comparative observational study was conducted in ICU and non ICU for a period of 6 months. The sample size of the study was 120. The data were collected, analyzed in terms of both inferential and descriptive statistics. Results: The incidence rate per thousand catheter days in non ICU was more as compared to ICU. The significant risk factors associated with CAUTI were the duration of catheterization and type 2 diabetes mellitus. The majority of the patients were catheterized for indications such as critically ill and unconsciousness followed by measurement of urine output. The outcomes of CAUTI were increased duration of hospitalization and recovery of patients. All the Gram-positive and Gram-negative isolates from non ICU were sensitive to piperacillin + tazobactam and meropenem. All the isolates from ICU and non ICU were resistant to co-trimoxazole. Conclusion: The urinary catheter is an essential part of modern medical care. Unfortunately, when used inappropriately or when left in place for too long, it is a hazard to the patient. This study helps to prevent indiscriminate and irrational use of antibiotics which contribute to emerging of drug resistance strains.